Carbon-coated SnO2 riveted on a reduced graphene oxide composite (C@SnO2/RGO) as an anode material for lithium-ion batteries. Issue 15 (24th February 2021) - Dai, Yao; Li, Fu; Fu, Yuan-Xiang; Mo, Dong-Chuan; Lyu, Shu-Shen
Abstract : The combined action of GO and glucose makes the SnO2 dispersed uniformly. The synergistic effect of the unique double-carbon structure can effectively improve the electrical conductivity of the SnO2 and strengthen lithium storage capability. Abstract : The research on graphene-based anode materials for high-performance lithium-ion batteries (LIBs) has been prevalent in recent years. In the present work, carbon-coated SnO2 riveted on a reduced graphene oxide sheet composite (C@SnO2 /RGO) was fabricated using GO solution, SnCl4, and glucose via a hydrothermal method after heat treatment. When the composite was exploited as an anode material for LIBs, the electrodes were found to exhibit a stable reversible discharge capacity of 843 mA h g −1 at 100 mA g −1 after 100 cycles with 99.5% coulombic efficiency (CE), and a specific capacity of 485 mA h g −1 at 1000 mA g −1 after 200 cycles; these values were higher than those for a sample without glucose (SnO2 /RGO) and a pure SnO2 sample. The favourable electrochemical performances of the C@SnO2 /RGO electrodes may be attributed to the special double-carbon structure of the composite, which can effectively suppress the volume expansion of SnO2 nanoparticles and facilitate the transfer rates of Li + and electrons during the charge/discharge process.